Innocence and Trust - Forgotten Concepts or Temporary Nuisances? - Gurevitz, Michael (European Journal of Applied Sciences, 2024)
Flourishing human societies owe their success primarily to the founding of efficient administration and supporting systems of communication, education, economy, security, and international relations. In addition, establishment of instructive principles of moral, ethical, and behavioral rules are also important in prevention of excessive aggression and violence. When these positive aspects are accompanied by decency, trust, good will, optimism and ambitious improvements, the citizen are satisfied and the entire community healthy.